Enhancement of a low-fidelity surgical simulator. Is it possible? - Evans, L M; Owens, D (Journal of Laryngology & Otology, 2021)
Background: Simulation training has become a core component in the training of ENT surgeons. It provides the opportunity for the repetitive practice of a surgical technique. Simulators are broadly categorised into low- and high-fidelity simulators. A method using a home microprocessor to enhance a low-fidelity surgical simulator is introduced. Method: The Yorick tonsil tie trainer was enhanced using an Arduino microcontroller attached to the simulated inferior pole of the tonsil. The Arduino was coded to give a visual stimulus when linear motion exceeded parameters. The prototype simulator was tested to gain information on whether the enhancement could identify differences between novice and expert users. Conclusion: An enhanced low-fidelity tonsil trainer was produced using a low-cost, simple home microprocessing board. The enhanced simulator gives objective feedback allowing for self-directed learning. Further research is required to evaluate the benefits of these enhancements above non-enhanced simulation training.